Consumer choice under limited attention when alternatives have different information costs - Frank Hüttner; Tamer Boyacı; Yalçın Akçay (European School of Management and Technology (ESMT), 2018)
Consumers often do not have complete information about the choices they face and therefore have to spend time and effort in acquiring information. Since information acquisition is costly, consumers trade-off the value of better information against its cost, and make their final product choices based on imperfect information. We model this decision using the rational inattention approach and describe the rationally inattentive consumer's choice behavior when she faces alternatives with different information costs. To this end, we introduce an information cost function that distinguishes between direct and implied information. We then analytically characterize the optimal choice probabilities. We find that non-uniform information costs can have a strong impact on product choice, which gets particularly conspicuous when the product alternatives are otherwise very similar. There are significant implications on how a seller should provide information about its products and how changes to the product set impacts consumer choice. For example, non-uniform information costs can lead to situations where it is disadvantageous for the seller to provide easier access to information for a particular product, and to situations where the addition of an inferior (never chosen) product increases the market share of another existing product (i.e., failure of regularity). We also provide an algorithm to compute the optimal choice probabilities and discuss how our framework can be empirically estimated from suitable choice data.
urn:nbn:de:101:1-201803146703; More recent version: http://hdl.handle.net/10419/183115
Keywords: D40; D80; 650; discrete choice; rational inattention; information acquisition; non-uniform information costs; market inference